Культивування кореневих мутантів Arabidopsis thaliana (L.) Heynh. in vivo - Adamchuk-Chala, N.I.; Bukhtiarova, L.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The information on morphological and anatomical features of Arabidopsis thaliana (L.) Нeynh. root mutants cultured in vivo and searching of an optimal conditions for plants growth is presented. The positive effect of presence into substrate of diatoms (Bacillariophyta) on A. thaliana plants growth and development is recorded.